The Colombian Zika Virus Isolate (COL345Si) Replicates in Prostate Adenocarcinoma Cells and Modulates the Antiviral Response (2022)
ABSTRACT: Zika virus (ZIKV), a flavivirus that is mainly transmitted by A. aegypti and A. albopictus and sexual transmission, has been documented and described. The ZIKV RNA detection in the semen of vasectomized men indicates that accessory glands such as the prostate could be a site of virus replication. In this study, we characterized the ZIKV infection, evaluated the antiviral profile, and demonstrated the AXL and TIM-1 expression on the PC3 prostate cell line. It was also determined that PC3 cells are susceptible and permissive to ZIKV infection without altering the cell viability or causing a cytopathic effect. The antiviral profile suggests that the PC3 cells modulate the antiviral response through the suppressor molecule expression, SOCS-1, during a ZIKV infection